2012
DOI: 10.1177/0748233712442712
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat-induced convulsion and death: a report of five cases

Abstract: Paraquat (PQ) is a potent toxicant for humans, and poisoning with PQ is associated with high mortality. Patients with severe PQ-induced poisoning may die of multiple organ failure involving the circulatory and respiratory systems. Death resulting from epilepsy-like convulsions, which are infrequently noted reported with PQ poisoning, is observed clinically with this condition. This study presents the clinical data of five patients with severe PQ-induced poisoning who died of epilepsy-like convulsions, and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Moreover, paraquat is a contact dihydropyridine herbicide which is extremely toxic to mammals, causing multiorgan failure and finally death (32). Paraquat has been reported to cause brain damage via formation of oxygen-free radicals (60), leading to neuronal cell death that finally causes disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, paraquat is a contact dihydropyridine herbicide which is extremely toxic to mammals, causing multiorgan failure and finally death (32). Paraquat has been reported to cause brain damage via formation of oxygen-free radicals (60), leading to neuronal cell death that finally causes disease.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat poisoning is characterized by multiple organ function failure, mainly involving the lung, kidney, heart, liver, and nervous system 16 . Yu et al observed that treatment with UA could protect neurons against excitotoxic and metabolic insults involving suppression of oxyradical accumulation, stabilization of calcium homeostasis, and preservation of mitochondrial function 17 .…”
mentioning
confidence: 99%
“…Viologen derivatives (4,4'-bipyridinium salts) were commonly used as non-selective herbicides (e.g. Paraquat) [18], but they can also cause severe or lethal poisoning in humans [19]. Interestingly, there are growing data indicating the association between chronic Paraquat exposure and Parkinson's disease [20][21][22].…”
Section: Introductionmentioning
confidence: 99%